Constitución del usufructo como forma alternativa para sustentar el pago de pensiones alimenticias. - Jadán Pesantes, Jenny Carolina (2023)
The present investigative topic, entitled: “Constitution of the usufruct as an alternative way to support the payment of alimony pensions” Treated the Ecuadorian reality regarding the right of food, by which minors ensure their right to life and quality of life, by demanding the parent who does not have tenance to provide a determined alimony through legal mechanisms, in order to be able to cover the common expenses of childhood, such as: education, health, leisure, mobilization, among others. However, the nuance of the research work was oriented to analyze the non-compliance in the payment of food pensions, a recurring situation in Ecuador where there is statistics of the year 2021 that reflects that 35% of debtors are in default. As can be appreciated, the national reality requires that the Law put forth sufficient legal contingents to ensure the collection of a right that guarantees the survival of the child-youth group, among which is the constitution of the established usufructo so that, if the debtor possesses any property, this is constituted in usufruct so that the product is used exclusively in the payment of alimony pensions, thus avoiding the delay or failure to comply. From this situation, the research problem arises: To what extent can the constitution of the usufruct guarantee the payment of alimony pensions? Making clear reference to determine whether the usufruct constitution is a correctly normated figure that enables the collection of alimony pensions or, in turn, if the figure has technical and legal problems that make it difficult to effectively collect pensions. In this way, the general objective of the present work was to analyze the constitution of the usufruct as a way to guarantee the payment of alimony pensions. The methodology corresponds to a qualitative approach that supports the analysis of doctrine and positive law. As well as, it has a quantitative approach that helps to process the data obtained from surveys; that is, the focus is what - quantitatively. On the other hand, the scope of the present study corresponds to one of descriptive type. The type of 15 research is propositive. The methods used are analytical and deductive. The research technique will be based on survey and documentary analysis, so the research instruments are: Survey Guide and Observation Guide. At the end of the work, the main conclusions and recommendations were reached. Key words: right of alimony, integral development of the child, constitution of usufruct, delay or failure to pay alimony pensions.